Photovoltaic System with SEPIC Converter Controlled by the Fuzzy Logic - Meryem Oudda; Abdeldjebar Hazzab (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
In this work, a fuzzy logic controller is used to control the output voltage of a photovoltaic system with a DC-DC converter; type Single Ended Primary Inductor Converter (SEPIC). The system is designed for 210 W solar PV (SCHOTT 210) panel and to feed an average demand of 78 W. This system includes solar panels, SEPIC converter and fuzzy logic controller. The SEPIC converter provides a constant DC bus voltage and its duty cycle controlled by the fuzzy logic controller which is needed to improve PV panel’s utilization efficiency. A fuzzy logic controller (FLC) is also used to generate the PWM signal for the SEPIC converter.